De novo exon 1 deletion of AUTS2 gene in a patient with autism spectrum disorder and developmental delay: A case report and a brief literature review. (6th April 2015) - Liu, Yi; Zhao, Dongmei; Dong, Rui; Yang, Xiaomeng; Zhang, Yanqing; Tammimies, Kristiina; Uddin, Mohammed; Scherer, Stephen W; Gai, Zhongtao
Abstract : Exonic deletions disrupting the autism susceptibility candidate 2 ( AUTS2 ) gene have been demonstrated as causal variants leading to neurodevelopmental disorders (NDDs) such as autism spectrum disorder (ASD) and developmental delay (DD). Here, we report on 830 kb de novo deletion at chromosome 7q11.22 in a 4‐year‐old male patient with ASD and DD. This deletion disrupts the promoter region and exon 1 of AUTS2, potentially leading to complete haploinsuffiency of the gene. In addition, we discuss the clinical presentation of the de novo deletion in the light of the previous studies describing deletions of AUTS2 in NDDs. © 2015 Wiley Periodicals, Inc.